Monte-Carlo Modelling For Evaluation Of Two Different Calculation Algorithms - Baljeet Seniwal; Telma C. F. Fonseca; Ranjit Singh (Brazilian Journal of Radiation Sciences, 2019)
Modeling of linac head (VARIAN Trilogy) for 6 MeV photon beam was performed using BEAMnrc code package (BEAMnrc 2017). The DOSXYZnrc code was used to determine the percentage depth dose (PDD profiles) and beam profiles for different symmetric square field sizes, i.e., 5cm X 5cm; and 40cm X 40cm. The DICOM images of Alderson Radiation Therapy (ART) RANDO Phantom was used. Four field 3D-CRT treatment plans were generated using AAA, PBC, and Monte-Carlo (MC). It was found that nominal energy of 5.7 MeV with FWHM of 1.2 mm provides best matching of modelled and working linac. All three 3D-CRT plans calculated with AAA, PBC and MC on a Pelvic Rando phantom, were compared using CERR (Computational Environment for Radiotherapy Research) and MATLAB 2013b. It was found that AAA and PBC have comparable results, although in case of tissue interfaces and inhomogeneous media AAA provides better accuracy in comparison to PBC. It can also be observed that AAA and PBC underestimate doses in comparison to MC in the soft muscle tissue which includes OARs such as bladder, bowel bag, and PTV TOTAL. It was found that both AAA and PBC fails to account for tissue air interface accurately and shows variation of 30-40% whereas for surface dose variation of +/-10% was observed. In homogeneous media (muscle tissue) AAA and PBC underestimate doses in comparison to MC. These commercially available algorithms overestimates and underestimates dose values as compared to MC based dose calculation for low and high dose regions specially.